The Impact of Menstrual Hygiene Products on Physical Fitness, Comfort, and Hygiene Practices among Female Athletes in Sri Lanka - N.G. Madhusha Dilini Subhashini; P. C. Thotawaththa (CV Media Inti Teknologi, 2026)
Background: Female athletes require proper menstrual hygiene management to maintain comfort, hygiene, and performance during physical activity. Products such as sanitary pads (SP), tampons (T), menstrual cups (MC) and others are commonly used, with selection influenced by various factors. This study examined the impact of menstrual hygiene products on physical fitness (PF), comfort (C), and hygiene practices (HP) among female athletes in Sri Lanka. Methods: Forty female athletes (n = 40), mean age (23.33 ± 3.38) years, were selected through purposive sampling from Volleyball (06), Gymnastics (03), Swimming (08) and Athletics (23). C and HP data were collected through a Structured Questionnaire and PF was assessed through the 30m sprint (30m S), vertical jump (VJ), Agility T-test (ATT) and the 12-minute Cooper test (12C). Non – parametric Kruskal – Wallis tests (SPSS version 21; p = 0.05) were applied due to non – normal data distribution. Result: Results indicated a statistically significant difference in the ATT score (p = 0.045), indicating variations in agility performance among product users. No significant differences were found in the results of the 30m S (p = 0.158), VJ (p = 0.735), or 12C (p = 0.763). Comfort levels were significantly higher among MC users (p = 0.003). Moreover, there were significant differences in HP, with MC users reporting better practices (p = 0.012). Conclusion: Finally, athletes using T and MC reported higher satisfaction than those using SP, with a significant preference for these products. MC and T were associated with higher comfort levels, better HP and improved physical performance, while pads were found to limit comfort and mobility, particularly during sports activities.